Everything to gain. A secret affair - Bradford, Barbara Taylor (New York : Avon Books, 2006)
Everything to gain. With wealth, a beautiful home, a caring, supportive husband, and two wonderful children, Mallory Keswick's life is a constant joy -- until her spirit is brutally tested, forcing her to discover new reserves of courage and strength when violent tragedy leaves her with nothing more to lose and . . . everything to gain.
A secret affair. In Venice, a chance encounter between a fearless television war correspondent and a lovely, unhappily married glass designer from New York leads to unanticipated affection, irresistible passion, and . . . a secret affair.
"2 novels in 1 volume"--Spine.
Keywords: Man-woman relationships -- United States -- Fiction; Love stories